2013
DOI: 10.1016/j.joca.2012.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Tibial coverage, meniscus position, size and damage in knees discordant for joint space narrowing – data from the Osteoarthritis Initiative

Abstract: SUMMARY Introduction Meniscal extrusion is thought to be associated with less meniscus coverage of the tibial surface, but the association of radiographic disease stage with quantitative measures of tibial plateau coverage is unknown. We therefore compared quantitative and semi-quantitative measures of meniscus position and morphology in individuals with bilateral painful knees discordant on medial joint space narrowing (mJSN). Methods A sample of 60 participants from the first half (2,678 cases) of the Ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 42 publications
8
89
0
Order By: Relevance
“…In a previous study, with double contrast macro‐radiographs, it was demonstrated that in the medial compartment, articular cartilage damage of the tibia was markedly attached to meniscal damage contrary to femoral cartilage 41. One of the limitations of our study is that we performed only cartilage measurements at the tibia because it was demonstrated that tibial coverage by the meniscus and femur cartilage thickness explained 80% of the variability of joint space width 42. The Kellgren Lawrence classification is known to have low reproducibility and moderate sensitivity 43.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, with double contrast macro‐radiographs, it was demonstrated that in the medial compartment, articular cartilage damage of the tibia was markedly attached to meniscal damage contrary to femoral cartilage 41. One of the limitations of our study is that we performed only cartilage measurements at the tibia because it was demonstrated that tibial coverage by the meniscus and femur cartilage thickness explained 80% of the variability of joint space width 42. The Kellgren Lawrence classification is known to have low reproducibility and moderate sensitivity 43.…”
Section: Discussionmentioning
confidence: 89%
“…The Osteoarthritis Research Society International (OARSI) assessment scale of knee OA [15,16], have been adopted as a standard in many health systems and OA studies around the world. Measured by these scales, Joint Space Width (JSW) is commonly associated with OA stages [17,18], this measurements helps to see the density of the cartilage and the loss of it.…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal sizing is important in evaluating meniscal damage, extrusion, movement and tibial plateau coverage by the meniscus [1,2]. Pre-operative size matching of the meniscus is also critical for successful meniscal allograft transplantation [3].…”
Section: Introductionmentioning
confidence: 99%